Activity Areas or Conflict Episode? Interpreting the Spatial Patterning of Lice and Fleas at the Precontact Yup’ik Site of Nunalleq (Sixteenth to Seventeenth Centuries AD, Alaska) - Forbes, Véronique; Huchet, Jean-Bernard; McManus-Fry, Ellen; Gómez Coutouly, Yan Axel; Masson-MacLean, Julie; Masson-MacLean, Édouard; Ledger, Paul; Britton, Kate; Hillerdal, Charlotta; Knecht, Rick (Études Inuit Studies, 2019)
Archaeoentomological research at the precontact site of Nunalleq (sixteenth and seventeenth centuries AD), Southwest Alaska, has identified hundreds of lice and fleas that infested both the human inhabitants of the site and their canine companions. As lice are host specific, staying attached to the host’s hair or fur during the totality of their lifecycle, they are generally considered excellent indicators of activity areas. Fleas, however, are relatively less common in archaeological contexts and, since they are mobile and able to infest several different host species, their potential use in the spatial reconstruction of activities is more limited. At Nunalleq, the study of insects from the most recent archaeological contexts produced very different spatial distribution patterns for human lice, fleas, and dog lice. This article compares these archaeoentomological data with other datasets available for the site (carrion-feeding flies, human hair, fur, coprolites, projectile points, and pieces of clothing) with the aim of establishing the phenomena that produced the distinct spatial distributions observed.